The role of youth in the formati The role of youth in shaping the information society of well-being in Uzbekistan - Ahmedova, Р.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
The transition of the world into the new information age is described in the article. The theory of the information society of well-being is presented, and the trends of changes in modern society are studied. Secondary processing of data from published studies of various scientists and organizations has been made. A statistical analysis of the dynamics of Internet consumption in Uzbekistan is made, and the impact of the Covid-19 pandemic on the usual way of life, the development of information and communication technologies and the well-being of people is analyzed. Conclusions on the consequences of the pandemic are made, and the influence of young people on the formation of an information society of well-being is substantiated. This article explores the significant role of youth in shaping the information society in Uzbekistan at a time of rapid technological progress. The article begins by highlighting the global transition into the new information age and presents the theory of the information society of the welfare state. It delves into the study of social changes and trends associated with the emergence of information and communication technologies. Drawing on a wide range of published studies by various scholars and organizations, the article provides a comprehensive secondary analysis of existing data. It examines statistical trends in Internet consumption in Uzbekistan, with a particular focus on the impact of the Covid-19 pandemic on people’s daily lives, the development of information and communication technologies, and the general well-being of individuals